Potential Immune Indicators for Predicting the Prognosis of COVID-19 and Trauma: Similarities and Disparities - Fouladseresht, Hamed; Ghamar Talepoor, Atefe; Eskandari, Nahid; Norouzian, Marzieh; Ghezelbash, Behrooz; Beyranvand, Mohammad Reza; Nejadghaderi, Seyed Aria; Carson-Chahhoud, Kristin; Kolahi, Ali-Asghar; Safiri, Saeid (Frontiers in Immunology, 2022)
Although cellular and molecular mediators of the immune system have the potential to be prognostic indicators of disease outcomes, temporal interference between diseases might affect the immune mediators, and make them difficult to predict disease complications. Today one of the most important challenges is predicting the prognosis of COVID-19 in the context of other inflammatory diseases such as traumatic injuries. Many diseases with inflammatory properties are usually polyphasic and the kinetics of inflammatory mediators in various inflammatory diseases might be different. To find the most appropriate evaluation time of immune mediators to accurately predict COVID-19 prognosis in the trauma environment, researchers must investigate and compare cellular and molecular alterations based on their kinetics after the start of COVID-19 symptoms and traumatic injuries. The current review aimed to investigate the similarities and differences of common inflammatory mediators (C-reactive protein, procalcitonin, ferritin, and serum amyloid A), cytokine/chemokine levels (IFNs, IL-1, IL-6, TNF-α, IL-10, and IL-4), and immune cell subtypes (neutrophil, monocyte, Th1, Th2, Th17, Treg and CTL) based on the kinetics between patients with COVID-19 and trauma. The mediators may help us to accurately predict the severity of COVID-19 complications and follow up subsequent clinical interventions. These findings could potentially help in a better understanding of COVID-19 and trauma pathogenesis.